Exploring multimessenger signals from heavy dark matter decay with EDGES 21-cm result and IceCube. Issue 10 (12th October 2021) - Halder, Ashadul; Pandey, Madhurima; Majumdar, Debasish; Basu, Rupa
Abstract: The primordial heavy or superheavy dark matter that could be created during the reheating or preheating stage of the Universe can undergo QCD cascade decay process to produce leptons or γ as end products. Although these could be rare decays, the energy involved in such decay process can influence 21-cm signal of hyperfine transition of neutral hydrogen during the reionization era. We explore in this work, possible multimessenger signals of such heavy dark matter decays. One of which could be the source of ultra high energy neutrino (of ∼ PeV energy regime) signals at IceCube detector whereas the other signal attributes to the cooling/heating of the baryons by the exchange of energy involved in this decay process and its consequent influence on 21-cm signal. The effect of evaporation of primordial black holes and baryon scattering with light cold dark matter are also included in relation to the evolution of the 21-cm signal temperature and their influence are also discussed.